Alcoholysis features of lithium aluminum hydrides for its hydrolysis reaction at low-temperature. (8th August 2022) - Yang, Na; Fu, Chengcheng; Bu, Fanqi; Xu, Xuequan; Yao, Huchen; Cheng, Yonghong; Zhang, Jinying
Abstract: Lithium aluminum hydrides are promising hydrogen storage materials due to their high hydrogen storage density. Hydrolysis of LiAlH4 is an ideal path to reach the operating temperature (−40/60 °C) target released by department of energy without extra heating processes. Ethylene glycol is a common antifreeze agent ingredient for low temperature reactions. However, the reaction features of ethylene glycol with LiAlH4 are still unknown. Here, the reaction behaviors of ethylene glycol with LiAlH4 have been studied. The reaction of LiAlH4 powder with ethylene glycol has been found to be hindered by the thin layer alcoholysis products on the surface. The alcoholysis products have been found to be easily react with water to yield Li–Al layered double hydroxides. The alcoholysis products have been demonstrated to be Li–Al double layered alcoholates, which is analogous to Li–Al layered double hydroxides. The ethylene glycol groups in the alcoholysis products are easily substituted by –OH in the presence of water. Thus, only water is consumed from the antifreeze agents for low temperature hydrogen release. Graphical abstract: Image 1 Highlights: The alcoholysis reaction of LiAlH4 powder with ethylene glycol was hindered by the passivation product layer. The alcoholysis products have a layered structure with the basal lattice parameter of about 8.37 Å. The formation of layered structure followed the 2D diffusion-controlled and deceleratory nucleation mechanism. Protonation made ethylene glycol moieties in alcoholysis products easily substituted by –OH in water. Water will be the only consumed agent in the reaction of LiAlH4 with antifreeze agents at low-temperature.